2019
DOI: 10.1038/s41419-019-1372-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CALCB/RAMP1 axis inhibits growth of Ewing sarcoma

Abstract: Ewing sarcoma (EwS) is an aggressive cancer characterized by chromosomal translocations generating fusions of the EWSR1 gene with ETS transcription factors (in 85% FLI1). EWSR1-FLI1 induces gene expression via binding to enhancer-like GGAA-microsatellites, whose activity correlates with the number of consecutive GGAA-repeats. Herein we investigate the role of the secretory neuropeptide CALCB (calcitonin-related polypeptide β) in EwS, which signals via the CGRP (calcitonin gene-related peptide) receptor complex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…The expression of CGRP, the closely related peptide CGRP2, and CALCRL was increased in some tumor types compared to the corresponding healthy tissues [3,6,7]. CGRP stimulated proliferation and inhibited apoptosis of both normal and malignant cells [3,6,8,9,10,11], and promoted migration and invasiveness of some carcinoma cell lines [3]. Furthermore, CGRP may foster tumor growth through its ability to promote angiogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CGRP, the closely related peptide CGRP2, and CALCRL was increased in some tumor types compared to the corresponding healthy tissues [3,6,7]. CGRP stimulated proliferation and inhibited apoptosis of both normal and malignant cells [3,6,8,9,10,11], and promoted migration and invasiveness of some carcinoma cell lines [3]. Furthermore, CGRP may foster tumor growth through its ability to promote angiogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CGRP may foster tumor growth through its ability to promote angiogenesis [11]. Accordingly, knockdown of CALCB (which encodes CGRP2 and is activated by the Ewing sarcoma associated fusion protein EWSR1-FLI) or RAMP1 decreased growth of Ewing sarcoma cell lines in vitro and in a mouse xenograft model, and the small molecule CGRP antagonists MK-3207 and olcegepant reduced colony and sphere formation by Ewing sarcoma cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in transport such as ATOX1, a copper chaperone protein that functions as an antioxidant and is involved in breast cancer cell migration 41,42 and FXYD2, a sodium/potassium-transporting ATPase subunit whose increased expression in tumors may contribute to angiogenesis 43 , were hypomethylated in TN-DCIS and invasive breast cancer. Hypomethylation of signal transduction-related genes BDNF and CALCB have the potential to lead to a myriad of cellular responses associated with cancer such as cell growth and proliferation, angiogenesis, and inflammation 44,45 . Genes involved in pathways related to increased cell motility, PFDN1 and MADCAM1, were hypomethylated while a gene associated with increased cell adhesion, COL7A1, was hypermethylated in TN-DCIS and invasive stages of TNBC.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have revealed that CGRP can directly modulate development of various types of cancer, with a large amount of literature reporting the expression of the CGRP receptor complex in cancer cells (55)(56)(57). CGRP was demonstrated to be able to modify the chemokinetic abilities of a metastatic breast cancer cell line and increase the expression of its receptors (58).…”
Section: Cgrp In Cancer Developmentmentioning
confidence: 99%
“…In addition, it has been demonstrated that CGRP increased the invasive ability of prostate cancer PC-3 cells and an osteosarcoma cell line (13,50). Recently, Dallmayer et al (56) revealed that targeting the CALCB/RAMP1 (the receptor complex of β-CGRP) axis inhibited the growth of Ewing sarcoma cells. Despite the lack of studies on the role of CGRP in OSCC, several studies have revealed a wide distribution of CLR/RAMP1 in oral soft tissues, bones and dental tissues (59).…”
Section: Cgrp In Cancer Developmentmentioning
confidence: 99%